Narrativas da (trans)formação na travessia, da formação técnica à educação profissional - Minguetti, Juliana Maria da Silva (2020)
This paper aims to investigate processes of personal and professional (trans) training in the perception of students from the first classes of Health and Wel ness in a technical-vocational education institution in the interior of the State of São Paulo. We start from the fol owing guiding questions: What are the main personal and professional transformations observed by the participants due to the course taken? How was the crossing between being and becoming professional? The research is within the scope of (auto) biographical research in education (DELORY-MOBERGER, 2008, 2014; JOSSO, 2007, 2010; PASSEGGI, 2010, 2011, 2013), in studies on adult education (FREIRE, 1996; CANARY, 2000). As for the construction of sources and analyzes we resort to the studies of Flick (1992) and Bardin (1997). Ten students from the professional courses of Aesthetics and Massage Therapy participated in the research. The sources consist of 10 individual interviews (narratives); sensitized by the perceptions of these students after the presentations of the three community-oriented projects that are pil ars of the course. For the interpretation and analysis of the data we also used observations generated through the transcription of 02 reflexive groups; training notebooks of 02 participants and the researcher's field diary. The research focused on the articulation between pedagogical actions based on the pil ars of education for the 21st century (DELORS, 2003), the Institution's training marks (technical-scientific domain, critical view, entrepreneurial, sustainable and collaborative attitudes), and the teacher's experiences. -searcher in professional technical training (GRABOWSKI and RIBEIRO, 2010). The results of the analyzes reveal that this articulation allowed the development of the autonomy and the protagonism of the participants who recognize the importance of the training marks in their professional development and assume, as first classes, the role of educators in welfare and health.